A produção de resíduos agroindustriais para a produção de amiloglucosidade. Aspergillus awamori - Santos, Genoveva dos (2006)
Many types of agroindustrial wastes may be employed as substrate for enzyme production. Glucoamylase is an enzyme used by the food industry to elaborate, for example, glucose syrup. The glucoamylase production by fermentation processes may be done by Aspergillus awamori, because this microorganism is considered safe to be used in food industries. In the solid estate fermentation (SSF), the microorganism is inoculated in a substrate where the activity of water allows the growth and cellular metabolism; however that doesn´t exceed the maximum water holding capacity of the solid substrate. In this work it was studied the possibility of employing agroindustrial wastes (potato, carrot processing redidues and mixes of these residues), for glucoamylase production by the Aspergillus awamori NRRL 3112. The experiments were mde varying the following conditions: moisture levels of 90, 92 e 98%, fermentation time and agitation; moisture levels of 30, 50, 70 and 90%; supplementation with sources of nitrogen (level of 2,20g (NH4)SO4/Kg of substrate, with and without pH correction) and phosphorous (levels of 3,8, 7,6 and 11,4g Na2HPO4/Kg of substrate); determination of the enzymatic activity in different buffers: pH 4,2, 0,1M citrate-phosphate buffer pH 4,2, 0,02M acetate buffer. In the tested conditions, the time of 72 hours was the most apropriate for the fermentation and production of glucoamylase, being obtained up to 725,00 U/mL when potato processing wastes used. The agitation, as tested, was not efficient in the increment of the enzymatic activity. There were not great differences in the results of enzymatic activity with the studied moisture levels (90, 92 and 98%). In the experiments with moisture levels of 30, 50, 70 and 90%, the highest enzymatic activities verified were of 65,98 with 50% moisture for the carrot processing waste, 141,38 U/mL with moisture of 30% and use of the potato processing waste and 55,77 U/mL when teh substrate was prepared by mixing 50% of each wastes with moisture of 70%. In the experiments with substrate supplmented with sources of phosphorous, the best results of enzymatic activity obtanied they were 318,33% U/mL, with addition of 0,19 g of Na2HPO4/Kg for the substrate with potato processing waste, 33,33 U/mL when the carrot processing waste was ued with addition of 0,19 g of Na2HPO4/Kg for the substrate; and 125 U/mL was obtained when the substrate was a mix of 50% of each waste with addition of 0,19 g of Na2HPO4/Kg for the substrate. When phosfhorous and nitrogen sources was added, the best results obtained were of 875 U/mL with potato waste, without pH correction, being added 0,38 g of Na2HPO4/Kg for the substrate and without addition of nitrogen, 141,66 U/mL, with carrot waste, being added 0,38 g of Na2HPO4/Kg for the substrate, without addition of nitrogen and without pHcorrection. In the experiments with different buffer solutions, best results of enzymatic activity were of 51,66, 401,66 and 176, 66 U/mL, with carrot, potato wastes and their mix, respectively, being used the pH 4,2, 0,1 M citrate-phosphate buffer. It can be concluded that the use of those wastes as sources for production of glucoamylase is technically viable, contributing with the process of value aggregation to sub-products of the agroindustrial processing and avoiding the discard of these in the nature.